Using technology acceptance model to explore physicians’ perspectives of clinical decision support system alerts - Hsuan-Chia Yang; Yu-Chuan Li; Shuo-Chen Chien; Chia-Hui Chien; Chun-You Chen; Po-Han Chien; Chun-Kung Hsu (BMJ Health & Care Informatics)
Objective To examine factors influencing physicians’ perspectives of clinical decision support system (CDSS) alerts using the Technology Acceptance Model (TAM), focusing on perceived ease of use (PEOU), perceived usefulness (PU), attitude towards usage (AT), user satisfaction (US) and behavioural intention to use (BI).Methods This study was conducted in the outpatient departments of a single academic medical centre in northern Taiwan, involving 72 physicians who completed a structured TAM-based questionnaire. Seven physician’s characteristics (age, clinical experience, CDSS operating status, patient volume, consultation frequency, gender and specialty) were analysed for their influence on PEOU and PU. Multiple regression analysis assessed relationships among TAM constructs and external factors.Results Patient volume and age negatively affected PU and PEOU (eg, age vs PU: β=−2.38, p<0.05; patient volume vs PEOU: β=−2.64, p<0.01), while clinical experience positively influenced them (PEOU: β=2.11, p<0.05). TAM construct analysis revealed that PEOU positively influenced PU (β=0.67, p<0.001), AT (β=0.31, p<0.01), and US (β=0.35, p<0.001). No significant correlation was found between US and BI (p=0.96).Discussion Findings suggest that PEOU significantly affects physicians’ behavioural intention to use alerts, with high patient volume and older age lowering acceptance due to alert fatigue. Adaptive, context-aware CDSS alerts can improve usability and align better with clinical workflows, enhancing efficiency in high-demand environments.Conclusion This study highlights the need for context-aware, frequency-optimised alert designs to enhance CDSS acceptance, improve user experience and streamline clinical workflows.